Capybara: Microsecond-Scale Live TCP Migration - Choi, Inho; Wadekar, Nimesh; Joshi, Raj; Zhang, Irene; Ports, Dan R. K.; Li, Jialin (2023 Asia-Pacific Workshop on Systems, 2023)
Latency-critical µs-scale data center applications are susceptible to server load spikes. The issue is particularly challenging for services using long-lived TCP connections. This paper introduces Capybara, a highly efficient and versatile live TCP migration system. Capybara builds atop a deterministic, kernel-bypassed TCP stack running in a library OS to realize its µs-scale TCP migration mechanism. Using modern programmable switches, Capybara implements migration-aware dynamic packet forwarding and transient packet buffering, further reducing system interference during live TCP migration. Capybara can transparently migrate a running TCP connection in 4 µs on average. It improves the average migration host latency by about 12 times compared to a Linux kernel-based solution.